2020
DOI: 10.3389/fonc.2020.00512
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Intratumoral Heterogeneity of Immune Repertoires

Abstract: There is considerable clinical and fundamental value in measuring the clonal heterogeneity of T and B cell expansions in tumors and tumor-associated lymphoid structures-along with the associated heterogeneity of the tumor neoantigen landscape-but such analyses remain challenging to perform. Here, we propose a straightforward approach to analyze the heterogeneity of immune repertoires between different tissue sections in a quantitative and controlled way, based on a beta-binomial noise model trained on control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…It is also likely that dose and scheduling for improved immune and patient responses are disease-and treatment-specific (8,37), reflecting current recommendations for curtailing tumor growth that are dependent on the targeted tissue and disease. Available tissue was restricted to small regions within patient tumors (∼1 g), and thus we were unable to capture the well-characterized tumor heterogeneity within RCC and other tumor types (38,39). In addition, while we did observe peripheral changes to T cell repertoires following treatment, the duration of contraction and tumor-enriched clone frequency was not evaluated past 4 wk due to the nature of the study.…”
Section: Discussionmentioning
confidence: 98%
“…It is also likely that dose and scheduling for improved immune and patient responses are disease-and treatment-specific (8,37), reflecting current recommendations for curtailing tumor growth that are dependent on the targeted tissue and disease. Available tissue was restricted to small regions within patient tumors (∼1 g), and thus we were unable to capture the well-characterized tumor heterogeneity within RCC and other tumor types (38,39). In addition, while we did observe peripheral changes to T cell repertoires following treatment, the duration of contraction and tumor-enriched clone frequency was not evaluated past 4 wk due to the nature of the study.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has shown that there is intratumoral heterogeneity of the TCR repertoire ( 30 ). When extrapolating our bilateral tumor model to a clinical situation, where antitumor immune responses are longitudinally monitored by tumor biopsy, it is important to determine whether the difference in TCR repertoire between the bilateral tumors could be considered equivalent to that within one side of the tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that there is intratumoral heterogeneity of the TCR repertoire (20). When extrapolating our bilateral tumor model to a clinical situation, where antitumor immune responses are longitudinally monitored by tumor biopsy, it is important to determine whether the difference in TCR repertoire between the bilateral tumors could be considered equivalent to that within one side of the tumor.…”
Section: Resultsmentioning
confidence: 99%